Profile of Erythropoietin Use and Hemoglobin Levels in Chronic Kidney Disease Patients with Anemia Undergoing Hemodialysis - Irsan Fahmi Almuhtarihan; Triana Emilya Rosa; Nailis Syifa; Aghnia Fuadatul Inayah; Didik Hasmono (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2026)
Anemia is a common complication of chronic kidney disease (CKD) caused by decreased endogenous erythropoietin production. Exogenous erythropoietin is administered to increase hemoglobin levels; however, patient responses may vary. This research aimed to identify patterns of erythropoietin use and describe hemoglobin levels before and after hemodialysis in CKD patients with anemia. This retrospective observational study used a cross-sectional design and medical record data from CKD patients with anemia who underwent hemodialysis and received erythropoietin from January to December 2023 at R.T. Notopuro Regional General Hospital, Sidoarjo. Hemoglobin change was calculated as post-hemodialysis hemoglobin minus pre-hemodialysis hemoglobin within the same session. Hemoglobin levels before and after dialysis were analyzed using a paired t-test. The dosage profile was presented descriptively. We analyzed 40 patients: 23 males (58%), 17 females (42%), and 35 patients (86%) aged >44 years. All patients received erythropoietin: 37 patients (92.5%) received 2000 IU, and 3 patients (7.5%) received 3000 IU. The mean hemoglobin level increased from 8.70 ± 1.01 g/dL before hemodialysis to 8.93 ± 1.10 g/dL after hemodialysis, with a mean change of +0.23 ± 0.80 g/dL (p=0.075). Based on dosage, the hemoglobin change was +0.21 ± 0.82 g/dL in the 2000 IU group and +0.53 ± 0.40 g/dL in the 3000 IU group. The erythropoietin use profile was dominated by erythropoietin alpha at a dose of 2000 IU. Hemoglobin levels after one hemodialysis session showed a small and statistically insignificant increase.